The susceptibility pattern and distribution of blaOXA-23 genes of clinical isolate Acinetobacter baumannii in a tertiary hospital, Indonesia - Anggraini, Dewi; Kemal, Rahmat Azhari; Hadi, Usman; Kuntaman, Kuntaman (The Journal of Infection in Developing Countries, 2022)
Introduction: Acinetobacter baumannii, a pathogen of concern in hospitals worldwide, has diverse antimicrobial resistance mechanisms leading to limiting the antibiotic options and carbapenemase enzyme production is one of the common mechanisms in carbapenem resistance. The epidemiology and resistance pattern of clinical isolates are critical in developing a prevention and treatment strategy. The aim of this was to determine the prevalence and resistance pattern of carbapenem non-susceptible strains (CNS) A. baumannii at Arifin Achmad General Hospital, Pekanbaru, Indonesia. Methodology: Data were retrieved from the culture and susceptibility test results from various clinical specimens from January 2015 to December 2019. A susceptibility test was conducted using Vitek 2 Compact following the manufacturer’s protocol. To explore the genetic profile of CNS A. baumannii, we amplified the blaOXA-23 and blaOXA-51 genes, carbapenemase producing genes, using a duplex polymerase chain reaction (PCR) among 24 isolates Chi-squared was used to assess the factors associated with the presence of CNS A. baumannii. Results: Between 2015-2019, 1.263 A. baumannii isolates were tested and the prevalence of CNS A. baumannii was 50%. The trend decreased from 53% in 2016 to 45% in 2019. The proportion of CNS A. baumannii was higher among samples from patients treated in the Intensive Care Unit (ICU) compared to non-ICU (p < 0.001). The CNS A. baumannii was also more frequently detected from sputum than from non-sputum samples (p = 0.009). CNS A. baumannii were highly resistant to almost all antibiotics and the highest susceptibility was to amikacin, tigecycline, and trimethoprim/sulfamethoxazole with 64%, 53%, and 43%, respectively. The blaOXA-23 gene was detected in 92% of tested CNS A. baumannii isolates. Conclusions: The prevalence of CNS A. baumannii is high at Arifin Achmad Hospital Riau, Indonesia. This is also supported by the high prevalence of the blaOXA-23 gene among tested isolates. Based on the antibiotic susceptibility pattern there are limited antibiotic choices for CNS A. baummannii urging the strengthening of antimicrobial stewardship programs in the country.